A review of mand frame training procedures for individuals with autism. Issue 2 (3rd July 2019) - Shea, Kerry; Sellers, Tyra P.; Brodhead, Matthew T.; Kipfmiller, Kailie J.; Sipila-Thomas, Emma S.
ABSTRACT: This review included a systematic search and analysis of studies targeting teaching mand frames to individuals with autism. Articles were selected through a search of databases limited to English language peer-reviewed articles. Using predetermined inclusion criteria, six studies were identified. Findings were summarized in terms of (a) participant, setting and publishing journals; (b) mand frame training procedures; (c) contriving establishing and abolishing operations; (d) generalization; and (e) varied responding. All six studies demonstrated that participants acquired targeted mand frame responses. Additional intervention outcomes, such as generalization and varied responding, also occurred in some cases. The need for future research and implications for practice are discussed.